An Examination of the Month-of-the-year Effect at Damascus Securities Exchange - Mouselli, Sulaiman; Al Samman, Hazem (International Journal of Economics and Financial Issues, 2016)
This paper explores the existence of the month-of-the-year effect in a newly established exchange of Damascus Securities Exchange (DSE). It employs Ordinary Least Squares Estimates (OLS) and dummy variables for the whole working period of the exchange from 2010 to 2015. This paper confirms the existence of positive and significant returns during May compared to remaining months. Average returns in May are six percent higher than average returns during the rest of the year. A possible explanation for May effect is dividend month premium suggested by <!--[if supportFields]><spanlang=EN-GB style='font-size:11.0pt;letter-spacing:-.2pt'><spanstyle='mso-element:field-begin;mso-field-lock:yes'>ADDIN CSL_CITATION {"citationItems" : [ { "id" : "ITEM-1","itemData" : { "DOI" : "10.1016/j.jfineco.2013.02.015","ISBN" : "0304405X", "ISSN" :"0304405X", "abstract" : "We find an asset pricinganomaly whereby companies have positive abnormal returns in months when theyare predicted to issue a dividend. Abnormal returns in predicted dividendmonths are high relative to other companies and relative to dividend-payingcompanies in months without a predicted dividend, making risk-basedexplanations unlikely. The anomaly is as large as the value premium, but lessvolatile. The premium is consistent with price pressure from dividend-seekinginvestors. Measures of liquidity and demand for dividends are associated withlarger price increases in the period before the ex-day (when there is no newsabout the dividend) and larger reversals afterward. ?? 2013 ElsevierB.V.", "author" : [ { "dropping-particle" :"", "family" : "Hartzmark", "given" :"Samuel M.", "non-dropping-particle" : "","parse-names" : false, "suffix" : "" }, {"dropping-particle" : "", "family" :"Solomon", "given" : "David H.","non-dropping-particle" : "", "parse-names" :false, "suffix" : "" } ], "container-title" :"Journal of Financial Economics", "id" :"ITEM-1", "issue" : "3", "issued" : {"date-parts" : [ [ "2013" ] ] }, "page" :"640-660", "publisher" : "Elsevier", "title": "The dividend month premium", "type" :"article-journal", "volume" : "109" },"uris" : ["http://www.mendeley.com/documents/?uuid=96761255-d802-4789-b411-c5f89e99f268"] } ], "mendeley" : { "formattedCitation" :"(Hartzmark & Solomon 2013)", "manualFormatting" :"(Hartzmark & Solomon, 2013)","plainTextFormattedCitation" : "(Hartzmark & Solomon2013)", "previouslyFormattedCitation" : "(Hartzmark &Solomon 2013)" }, "properties" : { "noteIndex" : 0 },"schema" : "https://github.com/citation-style-language/schema/raw/master/csl-citation.json"}<![endif]-->Hartzmark & Solomon (2013)<!--[if supportFields]><spanlang=EN-GB style='font-size:11.0pt;letter-spacing:-.2pt'><spanstyle='mso-element:field-end'><![endif]-->. Keywords: stock market efficiency, calendar seasonality, month-of-the-year effect, Damascus Securities Exchange. JEL Classifications: G11, G14, G19